Pyroptosis-related gene-based prognostic signature for predicting the overall survival of oral squamous cell carcinoma patients - Zeng, Deliang; Wang, Xiao; Zhang, Shuning; Zheng, Ao; Huang, Qingfeng; Cao, Lingyan (Frontiers in Surgery, 2022)
Purpose: Oral squamous cell carcinoma (OSCC) is a most common oral cancer in the world. Pyroptosis is a type of programmed cell death mediated by Caspase, accompanied by inflammatory response, and plays an important role in cancer progression. The purpose of this study was to explore and identify potential biomarkers in OSCC and further elucidate the potential role of cell pyrophosis in OSCC. Methods: First, we regarded the samples from The Cancer Genome Atlas (TCGA) database as a training dataset, and screened differentially expressed genes (DEGs), and further screened OSCC phenotypic characteristic genes by weighted gene co-expression network analysis (WGCNA). At the same time, the analysis of 42 known pyroptosis related genes showed that the pyroptosis related genes were widely expressed, mutated and methylated in OSCC samples. Results: Through correlation analysis, we identified OSCC pyroptosis-related DEGs. To further evaluate the prognostic value of pyroptosis-related regulators, we constructed a 7-gene based prognostic signature using Cox univariate analysis and LASSO Cox regression analysis. Meanwhile, we found that patients in the low-risk group had higher immune infiltration. Moreover, our results also indicated that there were significant differences in sensitivity to cisplatin and gefitinib between the high-risk and low-risk groups. Conclusion: Our study successfully constructed the pyroptosis related prognostic signature, playing a potential prediction role in OSCC prognosis, and also suggested that pyroptosis related regulators might be novel biomarkers for tumor diagnosis and treatment in OSCC.